Population characteristics and fecundity estimates of short-spined white sea urchin, Salmacis sphaeroides (Linnaeus, 1758) from the coastal waters of Johor, Malaysia - Rahman, Md. Aminur; Md. Yusoff, Fatimah; Arshad, Aziz; Sarker, S. M. Nurul Amin Harmuj Ali; Shamsudin, Mariana Nor (Academic Journals, 2013)
An attempt was undertaken to describe the size frequency distribution, length weight relationships and fecundity estimates of short-spined sea urchin, Salmacis sphaeroides from Peninsular Malaysia. In total 355 specimens of S. sphaeroides were collected from the inter-tidal shoal of Tanjung Kupang, Johor during the breeding season in March-August 2011. For each individual, the Total Length (TL) was measured using digital slide calipers and individual Body Weight (BW) was also taken through a digital balance. Mean length of S. sphaeroides was estimated as 72.85 mm and the mean weight was 143.01 g. Among the 355 specimens measured, 158 were males and 197 were females, indicating a sex ratio of 1 male to 1 female (1:1.25). The logarithmic form of length-weight relationship of S. sphaeroides was LogW = 2.4396xLogTL-2.3958. The exponential form of equation obtained for the length-weight relation was W = 0.004xTL2.4396. The value of regression co-efficient (R2) estimated for the species was 0.77. The mean fecundity was estimated at 7,676,000 (±247773) eggs. The regression coefficient between the absolute Fecundity (F) and Total Length (TL) was 0.76 and between the fecundity and drained body weight (DW) was 0.89; revealed linear regression model with a positive and significant relationship. This study represents the first time results on the total length-body weight relationships and fecundity estimates of this sea urchin from Peninsular Malaysia. The findings would immensely be helpful towards the understanding of growth patterns and fecundity, which will ultimately facilitate to develop the breeding, larval rearing and aquaculture of sea urchins.